(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article is about the emergence of the term “Samarkand” and the city of Samarkand. It is written about an unknown person named Samar. In addition, the role of the city of Samarkand in the history scene will be highlighted. It talks about the fact that it was the center of civilization and the changes that took place in the city over the centuries.